EKSPRESI EMOSI NEGATIF DALAM MEDIA SOSIAL (STUDI PADA KOMUNITAS ‘MARAH-MARAH’ DI TWITTER) - Azzahrani, Safira; Lukmantoro, Triyono; Manalu, S. Rouli (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2024)
Social media continues to grow rapidly and is closely related to the lives of people today. The various benefits obtained from the use of social media are certainly inseparable from its negative impact, which is related to the aspect of freedom. This research examines the phenomenon of individuals who behave violently and verbally aggressive on social media, focusing on the phenomenon that occurs in the Komunitas ‘Marah-Marah’ on Twitter. Komunitas ‘Marah-Marah’ is a community formed on Twitter by @musyihab on August 2022 that has received attention by users, indicated by the number of members reaching hundreds of thousands since it first appeared in 2022. This research aims to find out and explore a number of conditions that make individuals able to behave violently and verbally aggressive in the 'Marah-Marah' Community on Twitter, using a case study approach. Through interviews with six selected informants and pattern matching analysis method, the research has revealed a number of conditions that encourage individuals to behave verbally abusive, by exploring the concept of Online Disinhibition Effects by John Suler (2004). The results confirmed 5 elements of online disinhibition in forming disinhibition effects on individuals, which include: (1) Dissociative Anonymity; (2) Invisibility; (3) Asynchronicity; (4) Dissociative Imagination; and (5) Minimization of Authority, in the context of this study. In addition, it can be concluded that verbally abusive behavior shown through uploading tweets containing harsh words to vulgarity in the community, focuses more on expressing individual personal anger. This indicates that verbally abusive behavior that occurs on social media does not always target other people, but rather as a form of emotional release that cannot be expressed in real life.